Nitrogen Fertilizer Factory Effects on the Amino Acid and Nitrogen Content in the Needles of Scots Pine - Eugenija Kupsinskiene (The Scientific World Journal)
The aim of the research was to evaluate the content of amino acids in the needles of Pinus sylvestris growing in the area affected by a nitrogen fertilizer factory and to compare them with other parameters of needles, trees, and sites. Three young-age stands of Scots pine were selected at a distance of 0.5 km, 5 km, and 17 km from the factory. Examination of the current-year needles in winter of the year 2000 revealed significant (p